Cutaneous anthrax outbreak associated with use of cattle hides and handling carcasses, Amudat District, Uganda, 2023–2024 - Patrick Kwizera; Richard Migisha; Hannington Katumba; Esther Nabatta; Samuel Gidudu; Benon Kwesiga; Job Morukileng; Lilian Bulage; Alex Riolexus Ario (PLoS ONE, 2025)
Background Anthrax is a zoonotic disease that remains endemic in Uganda, particularly in cattle-keeping areas. On December 28, 2023, the first suspected human case of anthrax was detected in Amudat District. We investigated to determine the outbreak’s magnitude, identify risk factors, and recommend prevention and control measures. Methods We defined a suspected cutaneous anthrax case as acute onset of ≥2 of the following: skin lesions (papule, vesicle, or eschar) on exposed areas such as the hands, forearms, shoulders, back, thighs or face, localized itching, redness, swelling, or regional lymphadenopathy, in Amudat residents from December 2023–June 2024. A confirmed case was a suspected case with PCR-positive test for Bacillus anthracis . In unmatched case-control study (1:3 ratio), we compared exposures among 40 cases and 120 controls. We identified cases through house-to-house search, medical record reviews, and snowballing among case-persons. Human and animal samples were collected and tested, alongside an environmental assessment. We used multivariable logistic regression to identify associated risk factors. Results We identified 102 cutaneous anthrax cases, including 7 confirmed cases; none died. The outbreak lasted 7 months, peaking in March 2024, with an overall attack rate of 169/100,000 (males: 196/100,000; females: 138/100,000). Use of cattle hides as bedding (OR=12; 95% CI:2.7–52) and butchering cattle carcasses (OR=6; 95% CI:1.8–19) were significantly associated with anthrax. The highest infection risk was observed among individuals with multiple exposures: butchered only (OR = 6.9, 95% CI:2.6–18), butchered and carried cattle parts (OR = 11, 95% CI:1.2–96), butchered and skinned (OR = 14, 95% CI:3.5–56), and butchered, carried, and skinned (OR = 17, 95% CI:1.6–219). No livestock had been vaccinated prior to the outbreak. Conclusion The outbreak was associated to use of cattle hides as bedding and the butchering of cattle carcasses. We recommended community education, livestock vaccination, and safe carcass handling to prevent future outbreaks.